Nationalism, Democratisation and Primordial Sentiment in Indonesia: Problems of Ethnicity versus Indonesianness (the cases of Aceh, Riau, Papua and Bali) - Irine Hiraswari Gayatri (Journal of Indonesian Social Sciences and Humanities, 2010)
-